Pemberdayaan Masyarakat Tani Desa Suling Wetan Kabupaten Bondowoso Dalam Upaya Penyediaan Bibit Nilam Secara Mandiri - Mohammad Ubaidillah; Setiyono Setiyono; Slameto Slameto; Kacung Hariyono; Sri Hartatik; Sholeh Avivi; Parawita Dewanti; Agung Nugroho Puspito; Abdul Jalil (Journal of Community Development, 2025)
The majority of residents in Suling Wetan Village work as farmers and rely heavily on self-produced seeds due to the village’s remote location. One high-potential crop for marginal lands in the area is patchouli (Pogostemon cablin), a plant valued for its essential oil. However, the propagation of patchouli remains a significant challenge for local farmers due to limited knowledge and skills. This community engagement program aimed to enhance farmers’ capacities in patchouli propagation through a combination of awareness campaigns, technical workshops, hands-on training, direct field mentoring, and participatory monitoring and evaluation. Evaluation was conducted through direct observation and participant surveys. The results showed that 96% of participants gained a clear understanding of patchouli propagation techniques, and all participants acknowledged the importance of the program and expressed hope for its continuation. The activity successfully contributed to increasing farmers’ independence in sustainable patchouli seedling production.